Yo también quiero competir: las barreras de entrada y de permanencia y el procedimiento de eliminación de barreras burocráticas - Carrillo Temple, César Rodrigo (2020)
The exercise of the constitutional economic rights of free private initiative and freedom of enterprise may be justifiably limited by objective and reasonable limits established in regulation or imposed by the operation of the market itself. Nonetheless, such rights may be unjustifiably restricted by anti-competitive practices, regulations that contradict the legal system, or the imposition of unnecessary demands and limitations by the Government.In this context, the current regulatory framework in Peru establishes various mechanisms to control the different types of barriers to entry and permanence in the market, among which is the system of elimination of bureaucratic barriers, regulated by Legislative Decree 1256. In order to understand this system and its proper application, the author delimits the scope and particularities of the concept of bureaucratic barrier, as well as the requirements and demands for the individuals to report and prove the existence of illegal and/or unreasonable bureaucratic barriers before the Peruvian Competition Agency.